Intersectionality and group analysis : explorations of power, privilege and position in group therapy - Nayak, Suryia; Forrest, Alasdair (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Drawing on clinical practice, this book explores how the Black feminist idea of intersectionality is vital to all group work practices, including group analysis. Intersectionality enables exploration of power, position, and privilege in group work; this volume is an argument for the 'decolonizing' of therapeutic group training, practice, and institutional traditions. The wide range of contributors discuss the impact of intersectionality on their work within group analysis, from clinical examples to theoretical reflections. Chapters span topics such as leadership, racism, working with survivors of sexual violence and the experience of being a political refugee. Intersectionality and Group Analysis provides a space to develop clinically relevant theory for the future and includes an accessible introduction to the concepts of intersectionality. This essential text will be key reading for group analysts, other professionals working with and within groups, and readers looking to learn more about enhancing diversity within structures and organisations"--
Introduction : putting intersectionality to work / Suryia Nayak -- Holding the broken pieces : an intersectional approach to group analysis for women in prison / Anne Aiyegbusi -- Do black women's bodies matter in group analysis? Moving from double to intersectional consciousness / Anthea Benjamin -- The body of the group : sexuality, transgender, and group polyphony / Daniel Anderson -- This is how I came to live in stuckness : intersectionality, oppression & 'affectivism' as a group analytic intervention / Reem Shelhi -- An intersectional response to the intersectionality of trauma / Farideh Dizadji and Suryia Nayak -- Diffraction as the group-specific phenomenon / Alasdair Forrest -- Missing dialogues / Dick Blackwell & Claire Bacha -- Conclusion : a group analytic intersectional manifesto / Alasdair Forrest.
Keywords: Group psychoanalysis; Intersectionality (Sociology); PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Group